2019
DOI: 10.3390/su11133683
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Urban Morphology and Outdoor Comfort through Genetic Algorithm-Driven Urban Block Design in Dry and Hot Regions of China

Abstract: In areas with a dry and hot climate, factors such as strong solar radiation, high temperature, low humidity, dazzling light, and dust storms can tremendously reduce people’s thermal comfort. Therefore, researchers are paying more attention to outdoor thermal comfort in urban environments as part of urban design. This study proposed an automatic workflow to optimize urban spatial forms with the aim of improvement of outdoor thermal comfort conditions, characterized by the universal thermal climate index (UTCI).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…In order to overcome the lack of topological variability, other researchers have proposed sophisticated parametric modelling approaches to offering discrete formal variability of the generated building massing. One commonly used approach is to include several massing algorithms, respectively describing different building massing forms in one parametric model, and select one of these algorithms to create the building massing each time [6,24,25]. This approach is often used in design problems at the urban scale, and the desired urban form diversity can be simply achieved by varying permutations and combinations of different forms over multiple buildings.…”
Section: Parametric Modelling For Building Massing Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome the lack of topological variability, other researchers have proposed sophisticated parametric modelling approaches to offering discrete formal variability of the generated building massing. One commonly used approach is to include several massing algorithms, respectively describing different building massing forms in one parametric model, and select one of these algorithms to create the building massing each time [6,24,25]. This approach is often used in design problems at the urban scale, and the desired urban form diversity can be simply achieved by varying permutations and combinations of different forms over multiple buildings.…”
Section: Parametric Modelling For Building Massing Designmentioning
confidence: 99%
“…This approach is often used in design problems at the urban scale, and the desired urban form diversity can be simply achieved by varying permutations and combinations of different forms over multiple buildings. Nault et al [6] and Xiaodong et al [25] used this approach to create neighborhood-scale and urban block design based on a set of basic building forms for energy-daylighting optimization and outdoor thermal comfort optimization. Another approach is to create building massings composed of various small mass units.…”
Section: Parametric Modelling For Building Massing Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies usually started from constructing a relationship between the urban micro-climate and urban design to reveal how the urban morphology influences the urban micro-climate and, in turn, the energy usage [7,8]. Urban and building forms are the key factors that influence the urban micro-climate, such as solar radiation [9], wind environment [10], as well as the related energy demand [11,12]. Yuan et al highlighted the effect of the urban morphologies on the urban heat island (UHI) effect and integrated a geographic information system and computational fluid dynamics for modeling the impact of urban morphology on the heat dispersion [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that urban areas experience stronger warming trends than non-urban areas, demonstrating the notable effects of urbanization [3]. Xu et al [4] proposed an automatic workflow to optimize urban spatial forms with the aim of improving outdoor thermal comfort conditions as characterized by the universal thermal climate index, and applied this method in Kashgar, China. Ma et al [5] conducted field measurements and numerical simulations to analyze thermal sensation in a tourism area in Fo Shan city Many studies of indoor thermal environment/comfort were conducted in urban areas.…”
Section: Introductionmentioning
confidence: 99%